OBESITAS SEBAGAI FAKTOR RISIKO TERJADINYA DIABETES MELITUS PADA KARYAWAN UNIVERSITAS GADJAH MADA YOGYAKARTA - , SANTIKA BUDI ANDYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Obesity is known as a risk factor for several diseases, one of them is metabolic syndrome (diabetic mellitus, hypertension, dyslipidemia). This metabolic syndrome diseases can develop into cardiovascular disease when the disease is not handled properly. Objective : This research aims to find out how big that group obese are at risk for the onset of diabetic mellitus on employees of Universitas Gadjah Mada in Yogyakarta. Method : The methods used in the study is a prospective COHORT historitical method, in which the primary data used in this research is measuring blood sugar results data, height, weight, and distribution of questionnaire, while secondary data research data used was already made earlier in the year 2012. Therefore, this research is the continued research. The population was divided into two groups, the obese and non obese which is the measured blood sugar levels for diabetic mellitus. Research hypothesis was tasted by calculating the Relative Risk (RR) and the magnitude of the frequency of each risk factor for the occurrence of diabetic mellitus. Results : From prospective cohort historitical research, a group of employees who are obese have a trend a Relative Risk for occurrence of 4.92 time of risk factor for diabetic mellitus compared with the group of employees who are not obese. While the other risk factors of Relative Risk age â¥45 years old, consuming sugar >5sdm/week, physical activity â¤30 minute/day and emotional disorder (distress) is 5.67, 2.84, 1.92 and 3.18. Conclusions : Obesity groups have Relative Risk 4.92 multiplied by the risk of diabetic mellitus occurrence rather than non obesity groups.